The UMKM Product of Packaging Analysis as Selling Value in Entrepreneurship in Karo District - Muhammad Yunus (Tourism, Hospitality And Culture Insights Journal, 2021)
Business development in this era of globalization is inseparable from increasingly fierce competition in marketing products and services, as well as SMEs in marketing products that are packaged in such a way as to increase the selling value of the products being marketed. This study aims to see the extent to which product packaging attracts buyers from packaged products so that it can increase income for UMKM actors in tourist areas in Berastagi City, Karo Regency. The method used in this study is a descriptive research method with a quantitative approach, where UMKM actors are respondents in collecting data in this study. Where the results of the study show the UMKM product packaging variable is 2.681 > ttable 2.01808 and a significant value is 0.006 > from alpha 0.05, then H0 is rejected and H1 is accepted, thus partially the UMKM product packaging variable has a positive and significant effect on entrepreneurship.